Громадянська активність української студентської молоді: особливості виявлення та тенденції розвитку - Букрєєва, Ірина Вікторівна; Букреева, Ирина Викторовна; Bukrieieva, Iryna V. (Східноєвропейський національний університет імені Лесі Українки, 2013)
Важлива роль студентської молоді як майбутньої інтелектуальної еліти держави в становленні громадянського суспільства в Україні актуалізує дослідження змісту та стану громадянської активності студентства. За результатами опитування й глибинних інтерв’ю зі студентами-активістами Мелітополя виявлено, що зміст громадянської активності студентів зводиться до участі в університетських заходах, спрямованих на покращення їхнього життя та жодним чином не стосується виявлення їхніх політичних прав і свобод. Це пояснюється недовірою до владних структур та суспільно-політичних інститутів різного рівня, занепокоєністю з приводу власного майбутнього. The effective functioning of civil society is determined by the civic activism of the youth, particularly students as future of the intelligentsia. We conducted surveys, based on a combination of a questionnaire and in-depth interviews with student activists, by the laboratory of sociological research B. Khmelnitsky pedagogical university in order to identify the contents and condition of civic activity of students. The results of the poll found that young people participate in civic life mostly in the events organized by universities of city and their faculties. And they are aimed at improving the daily lives of students at the university, and in no way for the formation of social and political position. An essential factor in the formation of public activity is the education which now meets the criteria of professional training based on knowledge and information. Based on this, relevant, in our view, is the development and introduction of new approaches, methods, courses to prepare young people for life in the new environment of civil society, the purpose of which would be the formation of national consciousness as the basis of social consolidation and strengthening of the state.
Сivil Activity of the Ukrainian Student’s the Youth: Particularities of Manifestations and Tendencies of Development
Keywords: студентська молодь; громадянська активність; громадянське суспільство; політична участь; student’s the youth; civic activity; civil society; political participation